Bridging Tradition and Innovation: The Hail Desert Plant Database for Drug Discovery - Saeed, Mohd; Naaz, Sabiha; Tasleem, Munazzah; Alshammari, Nawaf; Kaur, Arminder; Alam, Mohammad Jahoor; Saeed, Amir (Indian Journal of Pharmaceutical Education and Research, 2024)
Introduction The Hail Desert Plant Database serves as an extensive repository that has been created to consolidate and systematize information concerning medicinal plants that are native to the arid Hail region in Saudi Arabia. Materials and Methods By conducting thorough literature mining from credible sources such as scientific articles and online databases, we systematically collected and organized data on more than 200 desert plant species. This comprehensive dataset includes botanical characteristics, phytochemical compositions, traditional applications, habitat preferences, documented medicinal uses, and the active compounds associated with these plants. In addition, we utilized molecular docking methodologies to perform computational investigations that aimed to elucidate the molecular interactions occurring between phytochemical compounds and target proteins that are known to be associated with the specific diseases traditionally treated by these plants. Results The database, which has been meticulously crafted to feature a user-friendly interface, offers an indispensable resource for researchers and clinicians who are captivated by the therapeutic possibilities presented by these arid florae. The inclusion of three-dimensional structures of docked complexes in the database significantly enhances its research capabilities, enabling comprehensive investigations and assisting in the development of potential drug candidates derived from natural sources. Conclusion The Hail Desert Plant Database serves as a crucial tool, facilitating progress in the field of drug discovery, investigations into structural biology, and the examination of alternative therapeutic agents derived from the diverse array of desert plants. The Hail Desert Plant Database is freely accessible at http://haildesertplants.com/.
Keywords: Desert plant database; Disease; Phytochemicals; Docked complex; Target protein